Coverage-Induced Chiral Transition of Co(II)-5,15-Diphenylporphyrin Self-Assemblies on Cu(111) - Xiang, Feifei; Schneider, M. Alexander (Journal of Physical Chemistry C, 2022)
Wallach's rule elucidates the phenomenon that racemic crystals are denser than their enantiopure form. The rule applies to most chiral molecular systems with the exception of some amino acids. However, it remains unclear whether Wallach's rule applies to the special but important class of chiral systems where chirality is induced by the adsorption of prochiral molecules on substrates. In this work, we show that the exemplary system, Cobalt(II)-diphenylporphyrin (Co-DPP) on Cu (111), follows Wallach's rule. Co-DPP assumes chiral isomers upon adsorption and shows a phase transition from an enantiopure linear chain structure to a racemic close-packed structure with increasing molecular density. Density functional theory (DFT) reveals that the chiral recognition, separation, and phase mixture of Co-DPP are due to the synergistic mechanism of substrate-molecule and molecule-molecule interactions.
CRIS-Team Scopus Importer:2022-05-13